Dehydration is a strong predictor of long‐term prognosis of thrombolysed patients with acute ischemic stroke. Issue 11 (18th October 2017) - Li, Sha‐Sha; Yin, Ming‐Ming; Zhou, Zhong‐He; Chen, Hui‐Sheng
Abstract: Background and Purpose: Dehydration was found to be involved in the poor prognosis of patients with acute ischemic stroke. It is unclear whether dehydration status before onset is related with prognosis of thrombolysed patients with acute ischemic stroke. If it is the case, quickly hydrating may improve the prognosis. The present study was designed to explore the issue. Methods: Eligible 294 patients with acute ischemic stroke after thrombolysis were enrolled in the present study according to inclusion/exclusion criteria. According to the modified Rankin scale (mRS) 90 days post stroke, the patients were divided into two groups: mRS 0–2 ( n = 191) and mRS 3–6 ( n = 103). In the present study, BUN/Cr ≥ 15 combined with USG > 1.010 or either of them were chosen as dehydration marker. Clinical data were analyzed between two groups. Univariate and multivariate statistical analyses were carried out. Results: Age, fibrinogen, blood glucose, BUN/Cr, NIHSS score at admission, the systolic blood pressure (SBP) before thrombolysis, dehydration status (BUN/Cr ≥ 15 plus USG > 1.010), hyperlipidemia, USG and D‐dimer on admission day, and TOAST classification showed significant difference between two groups ( p < .05). Further stratification analysis showed that BUN/Cr ≥ 15, NIHSS ≥ 6, blood glucose ≥8, and SBP > 150 were markedly associated with poor outcome (mRS 3–6, p < .05). After adjusting for age, fibrinogen, USG, D‐dimer, dehydration status, NIHSS, blood glucose, SBP, hyperlipidemia, and BUN/Cr at admission, multivariate logistic regression showed that dehydration status, higher NIHSS, higher blood glucose, and higher SBP at admission were independent risk factors for predicting the long‐term poor prognosis of thrombolysed patients. Conclusions: The present findings suggest that BUN/Cr ≥ 15 combined with USG > 1.010 as a marker of dehydration status was an independent risk factor for long‐term poor prognosis of thrombolysed patients with acute ischemic stroke. Abstract : Dehydration is a strong predictor of long‐term prognosis of thrombolysed patients with acute ischemic stroke.